New adventures in language and interaction - Streeck, Jürgen (Pragmatics & beyond ;, 2010)
In this book sixteen international scholars of language and social interaction describe their distinct frameworks of analysis. Taking conversation analysis and interactional sociolinguistics as their points of departure and investigating ordinary conversation as well as institutions such as health care, therapy, and city council meetings, they often incorporate gesture, prosody, and the listener's behavior in the analysis of talk. While some approaches are grounded in a critique of the major schools of interaction analysis, others integrate the interactionist perspective with ideas from fields.